How culture orientation influences the COVID-19 pandemic: An empirical analysis - Wang, Zhuo; Li, Yi; Xu, Ruiqing; Yang, Haoting (Frontiers in Psychology, 2022)
This study investigates how collectivism and individualism influences the COVID-19 Pandemic outcome based on the sociological theory of the Collectivism-Individualism culture dimension of Hofstede. Adopting an econometric model of cross-section regression, mediational analysis, and moderation analysis, a significant relationship was found that Collectivism-Individualism culture orientation influences the mitigation of the COVID-19 pandemic. It has also been found that policy responses mediate the cultural influence, and it is also moderated by other culture-related factors.